Species-Specific Structural Requirements of Alpha-Branched Trehalose Diester Mincle Agonists - Smith, Alyson J.; Miller, Shannon M.; Buhl, Cassandra; Child, Robert; Whitacre, Margaret; Schoener, Roman; Ettenger, George; Burkhart, David; Ryter, Kendal; Evans, Jay T. (Frontiers in Immunology, 2019)
Despite the ever present need for an effective Mycobacterium tuberculosis vaccine efforts for development have been largely unsuccessful. Correlates of immune protection against Mycobacterium tuberculosis are not wholly defined, but Th1 and likely Th17 adaptive immune responses have been demonstrated to be necessary for vaccine-mediated protection. Unfortunately, no approved adjuvants are able to drive a Th17 response, though recent clinical trials with CAF01 have demonstrated proof of concept. Herein we present the discovery and characterization of a new class of potential Th17-inducing vaccine adjuvants, alpha-branched trehalose diester molecules. Based off the Mycobacterium tuberculosis immunostimulatory component trehalose dimycolate, we synthesized and evaluated the immunostimulatory capacity of a library of structural derivatives. We evaluated the structure activity relationship of the compounds in relation to chain length and engagement of the Mincle receptor, production of innate cytokines from human and murine cells, and a pro-Th17 cytokine profile from primary human peripheral blood mononuclear cells. Murine cells displayed more structural tolerance, engaging and responding to a wide array of compound chain lengths. Interestingly, human cells displayed a unique specificity for ester chains between 5-14 carbons for maximal immune stimulating activity. Evaluation of two distinct alpha-TDEs, B16 and B42, in concert with a recombinant Mycobacterium tuberculosis antigen demonstrated their ability to augment a Th17 immune response against a Mycobacterium tuberculosis antigen in vivo. Collectively this data describes the species-specific structural requirements for maximal human activity of alpha-branched trehalose diester compounds and demonstrates their capacity to serve as potent Th17-inducing adjuvants.